Evidence-Responsiveness and Autonomy - Weimer, Steven (Ethical theory and moral practice, 2013)
It is plausible to think that part of what it is to be an autonomous agent is to adequately respond to important changes in one’s circumstances. The agent who has set her own course in life, but is unable to recognize and respond appropriately when evidence arises indicating the need to reconsider and perhaps adjust her plan, lacks an important form of personal autonomy. However, this “evidence-responsiveness” aspect of autonomy has not yet been adequately analyzed. Most autonomy theorists ignore it altogether and the few who have addressed it have failed to give a satisfactory account. In this paper, I first examine an evidence-responsiveness condition proposed by Arneson. I argue there that while Arneson’s condition provides a valuable framework in which to examine evidence-responsiveness, there are several crucial issues that it either fails to address at all or else fails to adequately resolve. That condition is therefore in need of further elaboration and refinement. I then examine a recent article in this journal by Blöser, Schöpf, and Willaschek which develops an account of autonomy that I argue can usefully be understood as employing and elaborating upon the general framework offered by Arneson. I argue that while the elaboration Blöser and her co-authors provide Arneson’s condition is instructive, it is inadequate in several important ways which indicate the form a more satisfactory evidence-responsiveness condition will take. I go on to develop such a condition and conclude by highlighting the advantages to be gained by including that condition in a complete theory of autonomy.